Equivalence of grain and forage composition in corn hybrid (Zea mays L.) from genetically modified off-patent (event TC1507) and non-genetically modified conventional corn - Hernan Darío Suárez Rodríguez; Diego Andrés Benítez Duarte; Alejandro Chaparro-Giraldo; Orlando Acosta (Agronomía Colombiana, 2022)
Off-patent corn (event TC1507) contains genes coding for CRY1F and PAT proteins, which confer resistance to lepidopteran insects and tolerance to the herbicide glufosinate-ammonium. We employed the substantial equivalence approach to investigate the compositional safety of the corn off-patent event (TC1507). The levels of the nutritional contents of proximate analytes in grain and forage tissues of off-patent genotypes of transgenic maize plants and conventional corn genotypes were compared. The levels of the analytes evaluated in the transgenic plants were found to be within the ranges published in the literature for non-transgenic corn and were statistically indistinguishable from the conventional corn from which they are derived (elite corn lines), indicating substantial equivalence between the off-patent (event TC1507) and its conventional counterpart. These results constitute key evidence of the safety evaluation of the world’s first transgenic corn developed from technologies that are in the public domain.